2017
DOI: 10.7717/peerj.3180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isolation method on doubling time and the quality of chondrocyte and osteoblast differentiated from murine dental pulp stem cells

Abstract: BackgroundStem cells are normally isolated from dental pulps using the enzymatic digestion or the outgrowth method. However, the effects of the isolation method on the quality of the isolated stem cells are not studied in detail in murine models. The aim of this study was to compare the matrices secreted by osteoblast and chondrocytes differentiated from dental pulp stem cells isolated through different means.MethodDPSC from murine incisors were isolated through either the outgrowth (DPSC-OG) or the enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…FTIR analysis revealed the presence of vibrational bands and P‐O stretching typically exhibited by ECM proteins based on previously described literature (Davies et al, 2017; Megat Abdul Wahab et al, 2017ahab et al, 2017). A significant single broad peak spanning 900–1200 cm −1 (P‐O peak) (refers to the formation of amorphous calcium phosphate (ACP; Davies et al, 2017)) was observed, indicating the formation of either calcium phosphate or hydroxyapatite on the surface of Si 3 N 4 and Ti6Al4V after just 30 days of in vitro study.…”
Section: Discussionmentioning
confidence: 90%
“…FTIR analysis revealed the presence of vibrational bands and P‐O stretching typically exhibited by ECM proteins based on previously described literature (Davies et al, 2017; Megat Abdul Wahab et al, 2017ahab et al, 2017). A significant single broad peak spanning 900–1200 cm −1 (P‐O peak) (refers to the formation of amorphous calcium phosphate (ACP; Davies et al, 2017)) was observed, indicating the formation of either calcium phosphate or hydroxyapatite on the surface of Si 3 N 4 and Ti6Al4V after just 30 days of in vitro study.…”
Section: Discussionmentioning
confidence: 90%
“…2D monolayer chondrocyte culture has a tendency to undergo dedifferentiation and have a higher probability to differentiate and form hypertrophic chondrocytes [25,26]. High density 3D micromass chondrocyte induction has been shown to secrete higher amounts of collagenous matrix and showed better cell differentiation behaviors [27,28]. Therefore, it would be a good idea to explore the combination of 3D micromass culture with bioceramic scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Doubling the time of the osteoblasts is dependent on seeding density. When seeded in the range of 10 3 cell/cm 2 density (as was done in this study), the doubling time is around 10 hours [18]. Therefore, four days of the experiment (96 hours) represent 10 doubling periods.…”
Section: Emf Stimulation Protocol Of the Cultured Osteoblast-like Cellsmentioning
confidence: 81%